STUDIUL ÎNCREDERII ÎN SINE LA ADOLESCENȚI - Jana RACU; Iulia RACU (Moldova State University, 2018)
Încrederea în sine reprezintă un factor decisiv în adaptarea socială și în dezvoltarea personalității. În acest context am realizat un studiu al încrederii în sine, al curajului social și al inițierii contactelor sociale la adolescenți. Am stabilit că un număr foarte mic de adolescenți prezintă un nivel înalt al încrederii în sine. Adolescenții sunt mai încrezuți în sine comparativ cu fetele. De asemenea, am stabilit relații între încrederea în sine și inițierea contactelor sociale. THE STUDY OF SELF-CONFIDENCE IN ADOLESCENCE Self-confidence at adolescents is one of the decisive factor in social adaptation and in personality development. In this context we realized a research of self-confidence at adolescents. The purpose of investigation was to highlight gender differences in self-confidence at adolescents and interrelation between self-confidence and social courage and initiation of social contacts. As results were established, only a small number of adolescents have high level of self-confidence. Boys have a more developed self-confidence than girls. Also we indentify relations between self-confidence and the initiation of social contact.